Cancer and breast cancer awareness interventions in an intellectual disability context: A review of the literature. (March 2021) - Walsh, S; O'Mahony, M; Lehane, E; Farrell, D; Taggart, L; Kelly, L; Sahm, L; Byrne, A; Corrigan, M; Caples, M; Martin, AM; Tabirca, S; et al.
Background: Women with an intellectual disability (ID) have a similar risk of developing breast cancer as women in the general population yet present with later stage breast cancers, which have poorer outcomes. Aim: To identify whether there is a need to develop a breast cancer awareness intervention for women with an ID. Methods: Interventions aimed at increasing cancer awareness and breast cancer awareness for people with an ID were identified and critically appraised. Results: Five interventions to increase cancer awareness or breast cancer awareness in people with an ID were identified. Conclusion: The review highlighted the paucity of theoretically underpinned breast cancer awareness interventions specifically aimed at women with an ID. Facilitating breast cancer awareness for women with an ID could potentially lead to earlier presentation of potential symptoms of breast cancer, earlier treatment, better prognosis and ultimately, improved survival. This article establishes that there is a need for an intervention underpinned by theory to increase breast cancer awareness in women with an ID.